The impact of communist party membership on wealth distribution and accumulation in urban China - Matteo Targa; Li Yang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper provides the first in-depth investigation into the evolution of the wealth gap between CCP and non-CCP households in urban China from 1995 to 2017. We apply unconditional quantile regression (UQR) to analyze the variations in the premiums of party membership across the wealth distribution. Our results show that although the average wealth gap between CCP and non-CCP households remained substantial and consistent throughout the period, there have been significant shifts in the returns structure of party membership over time. Prior to the housing reform in the 1990s, the highest wealth premiums of CCP households were primarily concentrated in the middle of the distribution, but now they are concentrated at the bottom of the distribution. This is mainly attributed to the fact that CCP households at the lower end of the net wealth distribution are more inclined to possess real estate assets, which tend to have higher value compared to those owned by non-CCP households. These effects fade out in the top half of the net wealth distribution, where the differences between CCP and non-CCP households become less apparent. Furthermore, by utilizing a balanced household panel from 2013 to 2017, we were able to track wealth accumulation at the household level. Our findings indicate that CCP households accumulate wealth faster than non-CCP households due to larger capital gains, and the differences between the two groups increase along the net wealth distribution
Keywords: G51; D31; P35; P36; 330; Wealth Accumulation; Wealth Distribution; Political Capital; CCP membership